If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + 5 = 13 Reorder the terms: 5 + 2c = 13 Solving 5 + 2c = 13 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2c = 13 + -5 Combine like terms: 5 + -5 = 0 0 + 2c = 13 + -5 2c = 13 + -5 Combine like terms: 13 + -5 = 8 2c = 8 Divide each side by '2'. c = 4 Simplifying c = 4
| x^2+19x+21=0 | | x-4*x^2=4 | | 5+2x=6-3x-1 | | 8n-(3n-5)=5-n | | x^2+8x-10=7x-4 | | x*5-79=x*2-10 | | Ax(23456+2384047)=100000000002022993 | | n-2=2+2n | | x/9=-2-(-6) | | kxab+mxac+nxad=(10a)(7b+4c-6d) | | -5/1+2(7-10)= | | x^3+x^2-69x-189=0 | | x^2-4x-2=3 | | -5/1++2(7-10)= | | 3(5-x)-4(3x-2)=3 | | 86-2x=25x+23 | | 139-5x=22x+22 | | 5x^2+8x=-19 | | 5x^2+8x=19 | | X+7=4(3x-2) | | 9-9x=45-16x | | 134x-(120000+82x)=560000 | | 5(8-3n)+5n=40+20n | | 9y=2x | | G=4(x+9)-(7+x)(x+1) | | (4b^3+9b^2-6)+(3b^3-9b+8)= | | Y+9=-2 | | 8(6x-1)=6x+1 | | -(6y+1)-(5y-8)=1 | | -79-10x=7*23 | | u-3u=10+8 | | y=-11+6x |